Sarcomere‐length dependence of myosin filament structure in skeletal muscle fibres of the frog. (3rd February 2014) - Reconditi, Massimo; Brunello, Elisabetta; Fusi, Luca; Linari, Marco; Martinez, Manuel Fernandez; Lombardi, Vincenzo; Irving, Malcolm; Piazzesi, Gabriella
Abstract : Key points: Contraction of skeletal muscle is thought to be regulated by a structural change in the actin‐containing thin filaments of the sarcomere, but recent results have suggested that a structural change in the myosin‐containing thick filaments may also be involved. We show that thick filament structure in resting muscle depends on the overlap with the thin filaments of the region of the thick filament containing myosin binding protein C (MyBP‐C). During isometric contraction, the regions of the thick filaments that do not overlap with thin filaments are highly disordered, in contrast to their helical order in resting muscle. The results provide strong support for the role of a structural transition in the thick filaments, mediated by an interaction between MyBP‐C and the thin filaments, in the physiological regulation of contraction in skeletal muscle. Abstract: X‐ray diffraction patterns were recorded at beamline ID02 of the European Synchrotron Radiation Facility from small bundles of skeletal muscle fibres from Rana esculenta at sarcomere lengths between 2.1 and 3.5 μm at 4°C. The intensities of the X‐ray reflections from resting fibres associated with the quasi‐helical order of the myosin heads and myosin binding protein C (MyBP‐C) decreased in the sarcomere length range 2.6–3.0 μm but were constant outside it, suggesting that an OFF conformation of the thick filament is maintained by an interaction between MyBP‐C and the thin filaments. During active isometric contraction the intensity of the M3 reflection from the regular repeat of the myosin heads along the filaments decreased in proportion to the overlap between thick and thin filaments, with no change in its interference fine structure. Thus, myosin heads in the regions of the thick filaments that do not overlap with thin filaments are highly disordered during isometric contraction, in contrast to their quasi‐helical order at rest. Heads in the overlap region that belong to two‐headed myosin molecules that are fully detached from actin are also highly disordered, in contrast to the detached partners of actin‐attached heads. These results provide strong support for the concept of a regulatory structural transition in the thick filament involving changes in both the organisation of the myosin heads on its surface and the axial periodicity of the myosin tails in its backbone, mediated by an interaction between MyBP‐C and the thin filaments.